(untitled) (Research, Society and Development, 2021)
To investigate the epidemiological behavior, sociodemographic aspects and factors related to the health-disease process of tuberculosis / HIV coinfection in the 4 states of Southeast Brazil, in a 10-year time series. This is a retrospective descriptive study with a quantitative approach of confirmed / reported cases of coinfection in southeastern Brazil. For data collection, the Disease Information System was consulted from 2007 to 2017, using TabWin as a tool for analysis of the variables of interest and the information obtained was tabulated with the help of EpiInfo 7.2 and Bioestat 5.3 softwares. A total of 317.188 records were analyzed, of which 45.552 cases of tuberculosis /HIV coinfection in southeastern Brazil. It was noted that 71.39% of individuals with both conditions (34.68%) and aged between 30 to 39 years (34.62%) and only 1.78% had completed higher education. Regarding the clinical manifestation,the pulmonary form was more frequent(66.06%) and that a large proportion of the co-infected patients were socially vulnerable due to illicit drug use (14.49%), alcoholism (14.51%) and smoking (6.95%), resulting in treatment abandonment (17.16%) and deaths from other conditions (16.06%). The epidemiological behavior of tuberculosis / HIV coinfection increased considerably over the 10-year period due to the lack of adherence to tuberculosis therapy, which can negatively influence the HIV serological result, leading to high morbidity and mortality due to these health problems.